Global warming impacts on rockfall frequency and magnitude due to changing frost distribution and frost cracking effectiveness - Birien, Tom; Gauthier, Francis; Meloche, Francis (Earth surface processes and landforms, 2024)
The distribution of freezing and thawing within rock masses is time varying (day to day or season to season) and controls the effectiveness of the frost cracking processes from the surface until various depths. These processes are major contributors to the development of rock instabilities. By altering the thermal regime of rockwalls, global warming could have a major impact on rockfall dynamic by the end of the 21st century. This study seeks to improve our understanding of the influence of this warming on (i) the distribution of freezing and thawing within rock masses, (ii) the effectiveness of frost cracking and (iii) the frequency and magnitude of rockfalls. Thermistor sensors inserted in a 5.5‐m horizontal borehole and a weather station were installed on a vertical rockwall located in the northern Gaspé Peninsula (Canada). This instrumentation was used to calculate the surface energy balance of the rockwall and to measure and model its thermal regime at depth over a period of 28 months. Combining locally recorded historical air temperature data with simulated future data (scenarios RCP4.5 and RCP8.5) made it possible to extend the rockwall thermal regime model over the period 1950–2100. The effectiveness of frost cracking over this 150‐year period has been quantified using a thermomechanical model. Depending on the scenario, warming of 3.3°C to 6.2°C is expected on the northern Gaspé Peninsula by the end of the 21st century. This rapid warming is likely to decrease the maximum depth reaches by the seasonal frost by 1–2 m and shorten its duration by 1–3 months. The frequency of freeze–thaw cycles could increase twelvefold in January. Frost cracking effectiveness should intensify around 70 cm in depth and disappear beyond that (RCP4.5) or diminish starting at 10 cm in depth (RCP8.5). In areas subject to seasonal freeze–thaw cycles, decimetric rockfall frequency could grow considerably in winter but be significantly reduced in fall and spring. Furthermore, frost cracking would cease contributing to the development of larger magnitude instabilities. Depending on the scenario, warming of 3.3°C (RCP4.5) to 6.2°C (RCP8.5) is expected on the northern Gaspé Peninsula by the end of the 21st century. By altering the thermal regime of rockwalls, the global warming could have a major impact on rockfall dynamic. In regions subject to seasonal freeze–thaw cycles, small magnitude rockfall frequency could grow considerably in winter but be significantly reduced in fall and spring. Frost weathering would cease contributing to the development of larger magnitude instabilities.